PENERAPAN MEDIA SMART BOX UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III MATERI BENTUK DAN SUMBER ENERGI - Octavia Dwi Widjayanti; Hendratno; Adika Hanafia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve the learning outcomes of class III students at SDN Wonokusumo IV/43 Surabaya through the application of smart box media in learning science and technology, material forms and energy sources. The research method used is Classroom Action Research (PTK) with two cycle stages starting from action planning to reflection on learning. Based on the research results, it was found that in the initial conditions or before being given action, there were 24 students (82.7%) who had not completed their studies and 5 people (17.2%) who had completed their studies with an average score of 41.7. In cycle I there were 17 students (58.6%) who had not completed their studies and 12 students (41.4%) who had completed their studies with an average score of 60.3. In cycle II there was an increase, namely: there were 26 students (89.6%) who had completed their studies and 3 students (10.3%) who had not yet completed their studies with an average score of 81.4. It can be concluded that the application of Smart Box media is effective in improving student learning outcomes regarding forms and energy sources.